Proceso de atención de enfermería aplicado a primigesta con embarazo de 40 semanas de gestación con preeclampsia severa - Morante Monar, Damian Elias (2018)
Throughout the world, hypertensive disorders are one of the most common complications of pregnancy and are responsible for a significant percentage of both maternal and perinatal morbidity and mortality, especially in low-resource settings. Preeclampsia, eclampsia and HELLP are complex syndromes with a wide variety in the severity of clinical symptoms and gestational age of onset. It must comply with the pharmacological treatment indicated by the doctor, initiate a low-sodium and low-fat diet, include foods rich in potassium in the diet; for its diuretic property favoring the elimination of excess salt in the body and nursing care; control of vital signs, comfort and education to the patient and family. Developing countries continue to experience comparatively higher rates of maternal and perinatal deaths from complicated pregnancies due to hypertension as a result of poor utilization of prenatal and obstetric care services as well as late presentation to specialized units for emergency care. The problems with the management of hypertension in pregnancy are found not only in the ignorance of its etiopathogenesis, but also in the variation in its definitions, measures and classifications used to categorize hypertension in pregnant women. In Ecuador, preeclampsia and eclampsia are the leading causes of maternal death from 2006 to 2014, and represent 27.53% of all maternal deaths (457 of 1660 occurred in that period).